Notes about the uses of plants by one of the last healers in the Basilicata Region (South Italy) - Montesano Vincenzo; Negro Donatella; Sarli Giulio; De Lisi Antonino; Laghetti Gaetano; Hammer Karl (Journal of Ethnobiology and Ethnomedicine, 2012)
Abstract Background The paper refers to the knowledge and uses of plants and to the linked ritual practices as referred by Matteo (It.‘Zì Matteo’, En. ‘Uncle Matthew’), one of the last elder healers in the Basilicata Region (South Italy). Particular attention is also paid to the uses of ‘Vruca’ (Tamarix gallica L.) as a medicinal and magical plant used to heal common warts on various parts of the body. Methods After obtaining prior informed consent, we collected data through an open interview about the uses of the plants and on the associated ritual practices. For each species, data were collected that included the vernacular names, preparation, plant parts utilized and their method of use. Results The uses of 52 taxa are described. Among these, 43 are or were employed medicinally, eight as culinary foodstuffs, and 4 for domestic, handicraft or ethnoveterinary uses. Among the major findings: the ritual and magical use of Tamarix gallica L. to heal warts is described in detail; so far, no records of similar use were found in any Italian ethnobotanical studies conducted in southern Italy. Conclusion Phytotherapy in the Basilicata region is practiced by elderly people who resort to medicinal plants for mild illnesses; we interviewed one of those traditional healers who is very experienced in the field, and possesses rich ethno-pharmacological knowledge.